2001
DOI: 10.1002/1521-3757(20011105)113:21<4124::aid-ange4124>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenylen-Dendrimere als empfindliche und selektive Sensorschichten

Abstract: Polyphenylen-Dendrimere sind monodisperse Makromoleküle, die auf Grund ihres starren Grundgerüsts stabile Hohlräume im Inneren bilden. Diese Eigenschaft unterscheidet sie von Dendrimeren, die aus flexiblen, aliphatischen Gruppen bestehen, und empfiehlt sie als attraktive Werkstoffe für die sensorische Überwachung flüchtiger Verbindungen mit Hilfe von massenempfindlichen Resonatoren, z. B. auf Basis von Quarz-Mikrowaagen (quartz microbalance, QMB). [1] Diese Form der Sensorik gewinnt in vielen Berei-durch Ionen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 27 publications
1
60
0
1
Order By: Relevance
“…[36] Qualitatively, the sorption behavior of the AuPPh films is equivalent to that of pure PPh dendrimer layers deposited onto QCMs. [25] This result shows that sorption of the analytes used in this study is mainly determined by the nature of the organic component of the film.…”
Section: N Krasteva Et Al/vapor Sorption Of Au Nanoparticle Compositesmentioning
confidence: 74%
See 1 more Smart Citation
“…[36] Qualitatively, the sorption behavior of the AuPPh films is equivalent to that of pure PPh dendrimer layers deposited onto QCMs. [25] This result shows that sorption of the analytes used in this study is mainly determined by the nature of the organic component of the film.…”
Section: N Krasteva Et Al/vapor Sorption Of Au Nanoparticle Compositesmentioning
confidence: 74%
“…[23][24][25] The sensor materials explored in this contribution combine the chemical selectivity of polyphenylene (PPh) dendrimers with the conductivity of gold nanoparticles, which enables direct electrical signal transduction. In a previous study we showed that coatings comprising Au nanoparticles and PPh dendrimers (AuPPh) respond very sensitively with a fast and reversible increase in resistance when dosed with volatile organic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Because the shape of the curve is similar to the Langmuir adsorption model, it is necessary to run the sensor in the appropriate span. Details of the characteristic concentration responses yield information about the associated adsorption enthalpy [9]. This has enabled the evaluation of many macromolecules and supramolecular aggregates containing structural units as outlined in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…33 As expected, the behaviour, and therefore applications, of rigid dendrimers such as polyphenylene ones is quite different compared with the flexible ones. 34 They for example do not show any backfolding of the arms (usually seen in all flexbile dendrimers) 35 leaving the central core of the molecules sterically accessible 36,37 and present a lower bulk density compared to the flexible one. 24 The interfacial properties of rigid dendrimers are also quite different than those of the flexible ones.…”
Section: Effect Of Dendrimer Rigiditymentioning
confidence: 99%